(2√3-√5)(√2+√3)=2√6+6-√10-√15(√a-√b)(a+√ab+√b)=a√a+a√b+√ab-a√b-b√a-b=a√b+√ab-b√a-b√12+1/(2-√3)-1=2√3+(2+√3)/(2-√3)(2+√3)-1=2√3+2+√3-1=3√3+1√(x/y+y/x+2)-√(y/x)-√(x/y)+√xy=√(√x/y+√y/
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 03:00:21
(2√3-√5)(√2+√3)=2√6+6-√10-√15(√a-√b)(a+√ab+√b)=a√a+a√b+√ab-a√b-b√a-b=a√b+√ab-b√a-b√12+1/(2-√3)-1=2√3
(2√3-√5)(√2+√3)=2√6+6-√10-√15(√a-√b)(a+√ab+√b)=a√a+a√b+√ab-a√b-b√a-b=a√b+√ab-b√a-b√12+1/(2-√3)-1=2√3+(2+√3)/(2-√3)(2+√3)-1=2√3+2+√3-1=3√3+1√(x/y+y/x+2)-√(y/x)-√(x/y)+√xy=√(√x/y+√y/
(2√3-√5)(√2+√3)
=2√6+6-√10-√15
(√a-√b)(a+√ab+√b)
=a√a+a√b+√ab-a√b-b√a-b
=a√b+√ab-b√a-b
√12+1/(2-√3)-1
=2√3+(2+√3)/(2-√3)(2+√3)-1
=2√3+2+√3-1
=3√3+1
√(x/y+y/x+2)-√(y/x)-√(x/y)+√xy
=√(√x/y+√y/x)^2-√(y/x)-√(x/y)+√xy
=√(x/y)+√(y/x)-√(y/x)-√(x/y)+√xy
=√(xy)
(2√3-√5)(√2+√3)=2√6+6-√10-√15(√a-√b)(a+√ab+√b)=a√a+a√b+√ab-a√b-b√a-b=a√b+√ab-b√a-b√12+1/(2-√3)-1=2√3+(2+√3)/(2-√3)(2+√3)-1=2√3+2+√3-1=3√3+1√(x/y+y/x+2)-√(y/x)-√(x/y)+√xy=√(√x/y+√y/
(√a-√b)(a+√ab+√b)
=a√a+a√b+√ab-a√b-b√a-b
=a√b+√ab-b√a-b
最后不对
=a√a+√ab-b√a-b
其他三个正确
√2*√3/√6=?
计算:√4-√3/√12+√3-√2/√6+√2-√1/√2=?
化简2√6/√2+√3-√5
√2*√3*√4*√5*√6*√7*√8等于多少,
求证:√(10+√24+√40+√60)=√2+√3+√5
求证:√(10+√24+√40+√60)=√2+√3+√5
√(5-2√6)+√(7-4√3)
(√2+√5-√3)/(2√30-6√2+4√3)
√(8+4√3)=√6+√2
(√6-√60)*√3-√1/2=?
化简3√ 2-√ 15+1/√ 3+√ 5+√ 6=
实数的运算 [急]√96-√24=√3(√3-1)=√20+√5/√5-√1/3*√2=√54=√2-5√1/2+√32=(√5-√2)平方=(√6-√2)(√2+√6)=|1-√2|+|√2-√3|+|√3-2|=√12*√6/√2=..
√5-√6-√20+√2/3+√9/5=
化简:(8+2√15-√10-√6)/(√5+√3-√2)
√56/√√14= -2/3√6= √2/2√3= 1/√3-√√2= 2-√√5/2+√5=
√24+√32/2√2-√27=?(3√18+1/5√50-4√1/2)/√32=?√24+√32/2√2-√27=?打错了应该是(√24+√32)/2√2-√27=?把√1+√112,√2+√11,√3+√10,√4+√9,√5+√8,√6+√7 从大到小排列起来,找出它的的
1/√3+√2+1/√4+√3+1/√5+√4+1/√6√5
|√5-√6|+√(√5-2)2次方-√(√6-3)²=